Value of percutaneous myocardial laser revascularisation in treatment of angina pectoris - Trębacz, Jarosław (2004)
Due to limitations of current therapeutic options of coronary artery disease there is still a group of patients with so called refractory angina pectoris. Methods of direct myocardial revascularization are under investigation. One of them is percutaneous myocardial laser revascularization (PMLR). Aim of our study was to determine value of percutaneous myocardial laser revascularization in treatment of refractory angina pectoris and to evaluate its effect on left ventricular function and myocardial perfusion. Since November 1999 to July 2003 fifty-eight patients have been referred to Department of Hemodynamics and Angiocardiography with diagnosis of refractory angina. Ultimately, 25 of them have been treated with PMLR. Study group undergone pre- and post procedural assessment with exercise treadmill test, perfusion exercise scintigraphy, dobutamine echocardiography and psychological evaluation. Till December 2003 post procedural testing after 1, 3, 6, 12 and 24 months undergone 24, 23, 22, 20 and 18 patients, respectively. Significant decrease of mean CCS score after 1 month post procedure was observed. In long-term, mean CCS score hasn’t changed significantly with trend toward increase. Mean duration of treadmill test increased significantly after 1 month. In long-term follow-up significant decrease in mean duration of exercise test was observed, but this value was still signif
Keywords: revascularisation; laser; angina pectoris